The effect of waste electronic plastics and waste marble dust as a partial aggregate replacement on concrete - Marattha, Niraj; Amatya, Iswar Man; Thapa, Kamal Bahadur (Journal of Innovations in Engineering Education, 2021)
Concrete is the most abundant material used in construction on present scenario where aggregates comprise of about three-fourth volume of concrete. On 2019, 28 Mt of E-waste generation was recorded in Nepal and its management has created a burden to the landfill sites. Also, marble dust is a waste obtained during processing and installation of marble which can be used as filler or fine aggregate in concrete for strength enhancement. Utilization of crushed E–waste plastics and waste marble dust in concrete will introduce a green and environment friendly method of construction without any compromise in the utility parameter and would represent positive effect to minimize the environmental degradation and replace naturally available aggregates which are continuously been used. The strength effects of waste electronic plastics and waste marble dust as aggregate replacement in concrete was studied in this research. For this study, 12 sets of concrete mixes were prepared with constant water cement ratio of 0.55. Marble dust was used as a sand replacement at 2.5%,5%,7.5% and 10% by volume of sand. Further 2 sets of 4% and 6% replacement of sand by marble dust was prepared to find out the optimum value as 5% replacement showed greater compressive strength. E-wastes plastics were then used as replacement to coarse aggregate at 1%, 2%, 3%, 4% and 5% along with 5% replacement of sand by waste marble dust. The workability test, compressive strength and flexural test of the mixes were determined. Based on the study, result showed that the compressive strength at 5% replacement of sand by marble dust was maximum while E-waste plastics replaced up to 4% had compressive strength greater than that of nominal mix concrete of grade M20. Flexural strength also increased of concrete containing E-plastic than that of normal concrete.